From rings to regions: modeling and mapping climate-driven timber production zones for Cyclocarya paliurus by integrating niche models and growth traits - Zhang, Zijie; Ye, Zhengyang; Shang, Xulan; Yang, Wanxia; Wang, Tongli; Fang, Shengzuo (Frontiers in Plant Science, 2025)
IntroductionCyclocarya paliurus, a native hardwood species with multi-functional value, has been prioritized in China’s National Reserve Forest Program. However, uncertainties related to its habitat stability and timber productivity under climate change pose challenges to effective conservation and afforestation planning aligned with national carbon neutrality goals.MethodsIn this study, we constructed species distribution models using Random Forest (RF) and Maximum Entropy (MaxEnt), based on verified field occurrence records and climatic data. Habitat suitability was projected under current and future climate scenarios (SSP2-4.5 and SSP5-8.5). We further analyzed the relationships between climate suitability and growth traits across 27 natural populations.ResultsBoth models demonstrated high predictive performance (RF AUC = 0.970, MaxEnt AUC = 0.942), identifying temperature variability and water availability as key limiting factors. Climate suitability was significantly correlated with 20-year diameter growth (R² = 0.625) and wood basic density (R² = 0.463). A stronger correlation was observed between annual growth and climate suitability of the preceding year (R² = 0.695), suggesting a lag effect.DiscussionBy integrating trait–climate relationships, we projected spatial shifts in fast-growing, high-quality timber zones. Future projections suggest a 49.2–60.0% decline in highly suitable habitats and timber forests by the 2050s, with marginal zones shifting northward and toward higher latitudes. This trait-integrated modeling framework offers a scientific basis for climate-resilient conservation and afforestation planning.